2019
DOI: 10.1186/s12920-019-0645-x
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 and CCNB1 as potential diagnostic markers of rhabdomyosarcoma: validation following bioinformatics analysis

Abstract: BackgroundRhabdomyosarcoma (RMS), a common soft-tissue malignancy in pediatrics, presents high invasiveness and mortality. However, besides known changes in the PAX3/7-FOXO1 fusion gene in alveolar RMS, the molecular mechanisms of the disease remain incompletely understood. The purpose of the study is to recognize potential biomarkers related with RMS and analyse their molecular mechanism, diagnosis and prognostic significance.MethodsThe Gene Expression Omnibus was used to search the RMS and normal striated mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…48 However, bioinformatics analysis exhibited that CCNB1 was significant up-regulated in F I G U R E 7 KEGG analysis of Neuro-2a cells infected by Ad-Pax3. KEGG pathways analysis revealed 'Parkinson disease', 'Protein processing in endoplasmic reticulum' and 'cell cycle' were significant KEGG pathways compared with untreated cells Rhabdomyosarcoma patient, 49 which was not consistent with the finding in Neuro-2a cells overexpressing Pax3. It indicated that CCNB1 may not be the direct target of Pax3.…”
Section: Transcriptome Analysis Of Neuro-2a Cells Overexpressing Pax3mentioning
confidence: 67%
“…48 However, bioinformatics analysis exhibited that CCNB1 was significant up-regulated in F I G U R E 7 KEGG analysis of Neuro-2a cells infected by Ad-Pax3. KEGG pathways analysis revealed 'Parkinson disease', 'Protein processing in endoplasmic reticulum' and 'cell cycle' were significant KEGG pathways compared with untreated cells Rhabdomyosarcoma patient, 49 which was not consistent with the finding in Neuro-2a cells overexpressing Pax3. It indicated that CCNB1 may not be the direct target of Pax3.…”
Section: Transcriptome Analysis Of Neuro-2a Cells Overexpressing Pax3mentioning
confidence: 67%
“…Besides, the overexpression of CDK1 promoted CRC cell proliferation, invasion and migration, indicating the promotive role of CDK1 in CRC development. Some researchers have found that CDK1 and cyclin B1 may be potential diagnostic biomarkers for rhabdomyosarcoma and hepatocellular carcinoma [16,17]. As discovered by Yamamura et al, phosphorylated CDK1 (p-CDK1), p-CDK2, cyclinB 1, and cyclinE 1 levels increase within cholangiocarcinoma tissues; in the meantime, P-CDK1 and cyclin B1 nuclear levels were positively correlated with the clinical stage as well as lymph node metastasis, while the expression of p-CDK 1 is related to poor patient survival [18].…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicated that knockdown of CCNB1 regulated by microRNA-144 signi cantly inhibited cell proliferation, migration, and invasion in HCC [31]. Besides, CCNB1 is also a promising biomarker for ER+ breast cancer [32] and rhabdomyosarcoma [33].…”
Section: Discussionmentioning
confidence: 99%